(untitled) (Al-Farooq Journal of Sciences, 2026)
This research provides an in-depth analysis of the features of the educational philosophy of the French philosopher Jean-Jacques Rousseau, which sparked an intellectual revolution, shifting the focus of education from the teacher and the curriculum to the child and their innate nature. The study examines the concepts of education and childhood, both linguistically and terminologically, highlighting Rousseau’s most prominent views, which advocate for the elimination of experimentation and reliance solely on simple sensory experience through rote learning and books. It also emphasizes the "natural" world, where all humans are equal under the umbrella of a good origin, as detailed in his book "Emile," which identifies three sources of education: nature, people, and things. The study divides the stages of child development and education into five advanced age stages, from infancy to adulthood, emphasizing the concept of "responsible education." Rousseau’s ultimate goal is to prepare a free individual capable of contributing to society, while favoring home-based education within a natural framework, contrasting it with corrupt social systems and enlightened social structures.